Missing Workforce: Some Personality Correlates of Absenteeism - Kumar, Kuldeep; Bakhshi, Arti (Prabandhan: Indian Journal of Management, 2010)
Workplace attendance and absenteeism are of fundamental importance to a progressive society. Absenteeism affects most directly all organizations as cost of production increases and productivity decreases, which has a direct bearing on the wealth generation process. It adds to the cost, or may reduce the quality of public and private goods and services. At the workplace, it may place additional burdens on employers and workers, especially at critically important times, or in key processes.